Sensibilidade de fungos termorresistentes aos sanitizantes e influência de diferentes condições sobre a eficácia antifúngica destes agentes - Stefanello, Andrieli (2021)
This study aimed to evaluate the sensitivity of thermoresistant fungi (Aspergillus australensis MB 2579; NFF 02; Aspergillus aureoluteus NFC1; Paecilomyces fulvus PFF 01; Paecilomyces niveus PNT 01; PNDC 01; PNB1 01; e Paecilomyces variotii PV 01; PV 01; PVCH 03) to a fumigant sanitizer (ortho-phenylphenol) to chemical sanitizers (benzalkonium chloride, biguanide, iodine, peracetic acid, and sodium hypochlorite) and electrolyzed water (acidic and alkaline) and to evaluate the influence of different variables (type, concentration, exposure time, temperature, and presence of organic load absence) on the effectiveness of chemical sanitizers against the standard strain for sanitization tests Aspergillus brasiliensis (ATCC 16404). To assess the sensitivity of thermoresistant fungi to electrolyzed water and chemical sanitizers, as well as to assess the influence of variables on the effectiveness of sanitizers, the tests were carried out in accordance with the standards of the European Committee for Standardization (CEN), with adaptations. For the tests using the sanitizing smoke generator against the thermoresistant species, the norms of the French protocol NF-T-72281, specific for disinfectants spread by air, were followed. Among the sanitizers tested against the thermoresistant species, the peracetic acid (1%) and the smoke generator based on orthophenylphenol showed the best results compared to the tested species. The opposite was observed for the sodium hypochlorite and biguanide sanitizers, which were ineffective in relation to most of the studied species. The different concentrations of electrolyzed water tested, in both acid and alkaline types, were ineffective and did not reach the minimum reduction of 3 log UFC required by regulation. In addition, it was observed that the thermoresistant species showed variation in sensitivity when exposed to different compounds. Regarding the study of intereferring factors, it was observed that all the variables tested influenced the antifungal efficacy of sanitizers against the standard strain Aspergillus brasiliensis (ATCC 16404). A presence of organic load was able to reduce a sanitizer efficacy by up to 1.5 log UFC. The concentration of product also had significant interference in the effectiveness of each compound, with the the maximum concentration recommended by the manufacturer reaching the best microbial inactivation but even then not achieving the regulation requirements in some cases. Some compounds such as iodine and peracetic acid were more effective at higher temperatures (40 °C), whereas benzalkonium chloride showed better efficacy at 10 °C. The compound exposure time was also an important factor, and the minimum time of 5 minutes was not enough to guarantee the compound efficacy, being recommended the exposure of at least 15 minutes. The findings of this study are important but additional studies evaluating the sensitivity of fungal species isolated from particular spoiled products to sanitizers currently used in the food sector under different situations are necessary. Mainly due to fungal tolerance to these compounds that are well established by studies carried out by our research group. Thus, it is essential to define the conditions to achieve maximum effectiveness of these products and success in the hygiene process.